Influence of Dimple Geometry on Coating Performance Under Uni-Directional Sliding. Issue 1 (September 2020) - Ananth, M Prem; Vijay, V; Dhinesh kumar, M; Kanna, G Kishore; Manoj, M
Abstract: The 316L stainless steel as very low carbon content than 316 steel alloys and 316L is material generally used for medical implant purpose and other industrial applications because of its excellent corrosion properties. The only disadvantage with 316L is it has poor wear resistance. By surface texturing the tribological properties can be improved. DLC (Diamond Like Carbon) Coating were made over the surface texturing. DLC Coating is a nano-composite coating which has unique properties of natural diamond low friction, high hardness, and also high corrosion resistance. Various dimple structures were made on the pin to study about its performance and the ideal dimple structure is selected by using pin on disc experiment. D2 Steel disc is taken as the counter-part for this experiment.